Behavior of several pseudomonas putida strains growth under different agitation and oxygen supply conditions. (17th April 2018) - Rodriguez, Alberto; Escobar, Sebastian; Gomez, Emilio; Santos, Victoria E.; Garcia‐Ochoa, Felix
Abstract : The growth rate of four strains of Pseudomonas putida, KT2440, KT2442, KTH2, and KTH2 (pESOX3), under different fluid dynamic conditions has been studied. The cultures were conducted in a stirred tank bioreactor by changing the stirrer speed. Several process variables, such as biomass concentration, dissolved oxygen concentration, oxygen mass transfer rate and oxygen uptake rate, have been measured or calculated. Also cell viability was determined by viable colony counting in Petri dishes and culture samples were subjected into a transmission electron microscopy analysis, in order to describe the integrity of the individual cells. The experimental results show that the genetically modified organisms, the strains KTH2 and KTH2 (pESOX3), present a different growth under low agitation conditions, and low oxygen supply level, while the growth of the wild type strains, KT2440 and KT2442, followed the typical sigmoidal evolution that could be described by the logistic equation. The presence of outer membrane vesicles has been observed in the GMO strains. When the cultures were conducted at low stirrer speed, and so at low oxygen transfer rate, these vesicles were detected, indicating the bacterial response to oxidative stress, caused by the catalytic activity of the HpaC enzyme. For all of the strains tested, no hydrodynamic stress has been detected, even at very high agitation levels. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:900–909, 2018